DETERMINATION OF PUBLIC ADMINISTRATION OF THE RIGHTS OF THE CHILD IN UKRAINE - Navrotskyi, O. O. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2017)
in the article on the basis of an analysis of the broad and narrow approaches to the definition of public administration that exist in modern science of administrative law, an author’s definition of public administration of child rights in Ukraine was proposed. Different views of scientists regarding related categories of public administration, namely public administration (in a broad and narrow sense) and public administration (in a broad and narrow sense) are analyzed. The argument is given regarding the prospects of normative consolidation of the doctrinal category of public administration in Ukraine, which is borrowed from the law of foreign states.